Relationship between Ergonomic Factors and Lower Back Pain on Dry Fish Processing Workers - Petrus Gawe Nusa Uran; Luh Putu Ruliati; Derviarbi Sakke Tira (Lontar : Journal of Community Health, 2022)
Low back pain is the oldest work-related health problem in history. The relationship between violent or violent and irregular movement and unnatural posture can cause structural damage. The purpose of this study was to analyze the ergonomic relationship to lower back pain complaints in dry fish processing workers in the fishing village of Oesapa. The type of research used in this research is quantitative research using analytical observation methods with a cross-sectional research design and design. The population to be studied are all dry fish fishermen in the Oesapa Fisherman Village, up to 50 workers. In the sampling technique, the total sample was used. The results of the study showed that there was no association between age and lower back pain complaints with a significant value (p= 0.108). There was an association between working hours and complaints of lower back pain with a significant value (p = 0.032). significant (p= 0.026). There was a significant association between work fatigue and complaints of lower back pain (p= 0.004). There was no association between working hours and complaints about back pain with a significant value (p= 0.480). There was a significant correlation between work attitudes and complaints of lower back pain (p= 0.035). There is no association between temperature and lower back pain complaints with a significant value (p= 0.395).